2003
DOI: 10.1165/rcmb.2002-0156oc
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species and Extracellular Signal-Regulated Kinase 1/2 Mitogen-Activated Protein Kinase Mediate Hyperoxia-Induced Cell Death in Lung Epithelium

Abstract: Therapy with high oxygen concentrations (hyperoxia) is often necessary to treat patients with respiratory failure. However, hyperoxia may exacerbate the development of acute lung injury, perhaps by increasing lung epithelial cell death. Therefore, interrupting lung epithelial cell death is an important protective and therapeutic strategy. In the present study, hyperoxia (95% O(2)) results in murine lung epithelium cell death by DNA-laddering, terminal deoxynucleotidyltransferase dUTP nick end labeling, and Ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
141
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(152 citation statements)
references
References 37 publications
6
141
1
4
Order By: Relevance
“…The presence of apoptosis of hyperoxic epithelium was evaluated by the presence of oligonucleosomal DNA fragments as assessed by terminal dUTP nick end labeling (TUNEL) analysis, and specific internucleosomal DNA laddering, immunohistochemical and biochemical assays for apoptotic gene expression and activities [12,25,26,[35][36][37][38][39]. In addition, increased caspase activities have also been observed in hyperoxic lungs by several investigators [12,38,40]. Caspase activation is considered to represent the onset of irreversible apoptotic pathway.…”
Section: Pulmonary Epithelial Cell Death In Hyperoxiamentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of apoptosis of hyperoxic epithelium was evaluated by the presence of oligonucleosomal DNA fragments as assessed by terminal dUTP nick end labeling (TUNEL) analysis, and specific internucleosomal DNA laddering, immunohistochemical and biochemical assays for apoptotic gene expression and activities [12,25,26,[35][36][37][38][39]. In addition, increased caspase activities have also been observed in hyperoxic lungs by several investigators [12,38,40]. Caspase activation is considered to represent the onset of irreversible apoptotic pathway.…”
Section: Pulmonary Epithelial Cell Death In Hyperoxiamentioning
confidence: 99%
“…Caspase-1, an important mediator in both apoptosis and inflammation, is activated in fractionated lysates of hyperoxic mouse lungs [34]. Exposure of caspase-3 deficient mice to hyperoxia for 72 hours induced less apoptotic cell death of lung epithelial cells, compared to that of the wildtype mice [12]. This suggests that caspase-3 activation is one of the critical steps in hyperoxia induced cell death.…”
Section: Pulmonary Epithelial Cell Death In Hyperoxiamentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 MEK and MKK are the upstream kinases for ERK1/2 and p38 MAPK, respectively. Recently, the MAP kinase pathways have been linked to hyperoxic toxicity in both cell cultures and animal models; 24,25 hyperoxia primarily activates ERK1/2 but less so p38. 25 Buckley et al have demonstrated that increased ERK1/2 may correlate with protection against hyperoxic toxicity in rats.…”
Section: Introductionmentioning
confidence: 99%
“…25 Buckley et al have demonstrated that increased ERK1/2 may correlate with protection against hyperoxic toxicity in rats. 24,26,27 p38 MAPK is linked to mismatch repair DNA response via the G2 checkpoint and to resistance to chemotherapeutic DNA-methylating agents. 28 The only study relating BER to cell cycle regulators demonstrates the link of long-patch BER to p21 in mouse embryonic fibroblast cell line.…”
Section: Introductionmentioning
confidence: 99%